Transcriptome analysis of calcium hydroxide tolerance in Enterococcus faecalis - Xu, Zhibo; Ma, Haonan; Jiang, Xinmiao; Baima, Quzhen; Zhen, Yuqi; Yang, Shipeng; Meng, Xiuping (Frontiers in Microbiology, 2025)
Calcium hydroxide (Ca(OH)2) is commonly used as a root canal disinfectant, but its effectiveness against Enterococcus faecalis is limited, likely due to the bacterium’s ability to tolerate it. This study aimed to investigate the underlying mechanism of E. faecalis tolerance to repeated exposure to Ca(OH)2. Initially, E. faecalis was exposed to Ca(OH)2 for 10 successive passages. The survival rate of the bacteria increased progressively, suggesting the development of tolerance to Ca(OH)2. Crystal violet staining revealed that calcium hydroxide-tolerant strains formed more robust biofilms compared to standard strains. To delve into the mechanisms of Ca(OH)2 tolerance in E. faecalis, RNA sequencing was employed for a preliminary investigation. Transcriptome sequencing identified 683 differentially expressed genes (DEGs) in the calcium hydroxide-tolerant strain, with 368 genes upregulated and 315 downregulated compared to the standard strain. Bioinformatics analysis revealed that the upregulated genes were associated with carbohydrate transport and metabolism, starch and sucrose metabolism, quorum sensing, aminoacyl-tRNA biosynthesis, and two-component systems signaling pathways. In contrast, the downregulated genes were primarily linked to lipoic acid metabolism, degradation of valine, leucine, and isoleucine, and the citric acid cycle (tricarboxylic acid cycle) signaling pathways. The findings suggest that prolonged exposure to Ca(OH)2 induces tolerance in E. faecalis. RNA sequencing further revealed that this tolerance involves multiple interconnected signaling pathways, providing a critical foundation for future research into therapeutic strategies for E. faecalis infections.